Histological assays on impact of Arsenic on the brain and Arsenic-induced mortality in Lucilia cuprina (Wiedemann, 1830) (Diptera: Calliphoridae) - Hasan, Sukanya; Hasan, Md Rakib; Amin, Saidul; Hasan, Md; Rimu, Khadija Begum; Ria, Nusrat Jahan; Begum, Murshida (Bangladesh Journal of Zoology, 2024)
The study investigated the effect of various arsenic concentrations on the brain tissue of L. cuprina employing histological slide preparations via feeding and injection treatments. Arsenic-induced mortality was observed across concentrations of 0.01 ppm, 0.05 ppm, 0.1 ppm, 0.5 ppm, and 1 ppm over a 72-hour period. Total mortality within this timeframe was corrected by using Abbott's correction formula.The mean mortality resulting from exposure to various concentrations of As in both cases was analyzed using Levene's test followed by one-way ANOVA by SPSS (v. 26) and the posthoc analysis was conducted by Duncan's Multiple Range Test. The highest mortality recorded at 1 ppm for both feeding (9.33±0.88) and injection (10.67±0.33) treatments. Conversely, the lowest mortality occurred at 0.01 ppm for both fed (1.67±0.33) and injected L. cuprina (2.33±0.33), indicating a positive correlation between mortality and arsenic concentration. Comparison of feeding and injection methods revealed consistently higher mortality with injection. Histological slide preparations revealed varying degrees of brain tissue degradation, categorized into four groups (A=0-30%, B=31-60%, C=61-80%, and D=81-100%). The highest mean of maximum affected brains (Category D) was observed at 1 ppm for both feeding (14.67±1.53) and injection (16.33±1.53), while the minimum affected brains (Category A) occurred at 0.01 ppm for feeding (17.67±0.58) and injection (17.00±1.00). The results highlight the importance of conducting thorough toxicological investigations that cover a range of metal contaminants, including arsenic, and involve diverse insect species. Bangladesh J. Zool. 52(1): 57-66, 2024